Effects of Dietary Beta-Carotene on Lung Function, Respiratory Symptoms and Chronic Obstructive Pulmonary Disease - Lee, Andy (Nova Science, 2013)
This chapter reviews the epidemiological evidence on the effects of dietary beta-carotene on lung function, respiratory symptoms, mortality and risk of developing chronic obstructive pulmonary disease (COPD). Published studies are located by searching several electronic databases using the relevant key words. High levels of intake of beta-carotene were found to improve lung function (forced expiratory volume in one second and forced vital capacity) and appeared to have some protective effects against respiratory symptoms such as dyspnea, cough and excessive phlegm. However, no tentative conclusion on the association between dieta1y beta-carotene and both the risk and mortality of COPD can be drawn. In view of the emerging epidemiological evidence, further clinical and experimental research is required to ascertain the role of beta-carotene on the aetiology of COPD.